2023
DOI: 10.2967/jnumed.122.264225
|View full text |Cite
|
Sign up to set email alerts
|

MIRD Pamphlet No. 28, Part 1: MIRDcalc—A Software Tool for Medical Internal Radiation Dosimetry

Abstract: Medical internal radiation dosimetry constitutes a fundamental aspect of diagnosis, treatment, optimization, and safety in nuclear medicine. The MIRD committee of the Society of Nuclear Medicine and Medical Imaging developed a new computational tool to support organ-level and suborgan tissue dosimetry (MIRDcalc, version 1). Based on a standard Excel spreadsheet platform, MIRDcalc provides enhanced capabilities to facilitate radiopharmaceutical internal dosimetry. This new computational tool implements the well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The calculation of RI for different radiopharmaceuticals, begins with estimates of the organ‐specific absorbed doses. To achieve this, we utilized reference radiopharmaceutical time‐integrated activity coefficients published in ICRP Publication 128 19 as input, calculations were performed using MIRDcalc software, 14 which yielded organs absorbed dose, E , E DW , LAR, and RI as output. The number of source regions used in each calculation was dependent on how the biokinetic data were provided in ICRP publication 128, but typically 4−8.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculation of RI for different radiopharmaceuticals, begins with estimates of the organ‐specific absorbed doses. To achieve this, we utilized reference radiopharmaceutical time‐integrated activity coefficients published in ICRP Publication 128 19 as input, calculations were performed using MIRDcalc software, 14 which yielded organs absorbed dose, E , E DW , LAR, and RI as output. The number of source regions used in each calculation was dependent on how the biokinetic data were provided in ICRP publication 128, but typically 4−8.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, the RI calculation for radiopharmaceutical applications is integrated into the newly released MIRDcalc nuclear medicine dosimetry software, 14 freely available at http://www.mirdsoft.org (example use cases of RI can be found in the MIRDcalc manual).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown variations in effective doses due to photons, electron [20] and 18 F-FDG [21] estimated using a voxel-based model from those estimated using stylized phantoms. The UF/NCI and PRC phantoms have been used to compute SAF values for electrons and photons of various energies [22][23][24], which in turn are used to compute S values and organ doses for medical intake scenarios [24,25]. These studies only focus on dose computation for medical protection pathways such as intravenous and oral administration, while leaving out the inhalation pathway required for radiological protection.…”
Section: Introductionmentioning
confidence: 99%
“…TO THE EDITOR: The journal has recently published MIRD pamphlet no. 28, parts 1 and 2, which describe and provide validation for the nuclear medicine software code MIRDcalc, part of the MIRDsoft.org series of freely accessible software for the field of nuclear medicine (1,2). We wish this letter to serve as an addendum clarifying an important technical aspect of the work in regard to some of the graphical presentations of the library of phantom computational models used to generate radionuclide S values, which form the computational engine of organ dosimetry in the MIRDcalc code.…”
mentioning
confidence: 99%